Biosorption characteristics of methylene blue dye by two fungal biomasses. Issue 3 (4th May 2021) - Bouras, Hadj Daoud; Isik, Zelal; Arikan, Ezgi Bezirhan; Yeddou, Ahmed Réda; Bouras, Noureddine; Chergui, Abdelmalek; Favier, Lidia; Amrane, Abdeltif; Dizge, Nadir
ABSTRACT: A novel approach has been tried to use both Aspergillus carbonarius (AC) and Penicillium glabrum (PG) fungi for the first time to remove methylene blue (MB) from aqueous solutions. The biosorption was favoured using a biosorbent concentration of 0.33 g/L at pH 8.2. Biosorption kinetics were evaluated for different dye concentrations (5–25 mg/L). The resulting biosorbent was characterised by scanning electron microscopy (SEM), X-ray diffractometer and Fourier transformer infrared spectroscopy (FTIR) techniques. The maximum biosorption capacities of AC and PG for MB were 21.88 mg/g and 16.67 mg/g, respectively at 30°C. The results suggested that A. carbonarius and P. glabrum could be used as biosorbents for the effective removal of methylene blue from dye wastewater in terms of biosorption capacity, availability and low cost.